Lung transplantation in the septuagenarian can be successfully performed though long‐term results impacted by diseases of aging. Issue 5 (27th January 2022) - Benissan‐Messan, Dathe Z.; Ganapathi, Asvin M.; Guo, Marissa; Henn, Matthew C.; Keller, Brian C.; Howsare, Molly; Rosenheck, Justin P.; Kirkby, Stephen E.; Mokadam, Nahush A.; Nunley, David; Whitson, Bryan A.
Abstract: Background: Advanced age is considered a risk factor for lung transplantation (LTX). We sought to evaluate the long‐term outcomes of LTX in the septuagenarian. Methods: LTX recipients in the UNOS transplant registry (May 1, 2005–June 12, 2020) were stratified into 18–59, 60–69, and > = 70 years of age. Recipient and transplant characteristics were evaluated for survival, cause of death (COD), length of stay (LOS), and complications. A Kaplan‐Meier analysis examined long‐term survival for all patients stratified by age, specifically looking at cause of death. Results: A total of 27 632 recipients were identified. As recipients aged, we found a decrease in proportion of cystic fibrosis and an increase in restrictive disease while obstructive disease peaked in the 60–69yo cohort ( P < .001). Septuagenarians had higher rates of single LTX, male gender, and white race ( P < .001). Older recipients had significantly longer donor recovery distances traveled with paradoxical shorter ischemic times, shorter hospital LOS and were transplanted at higher volume centers. There was no difference with in‐hospital mortality among groups ( P = .5). Acute rejection during initial hospitalization, rejection within 1 year, and post‐transplant dialysis incidence decreased with age. Graft failure was a common COD in younger patients while malignancy and cardio/cerebrovascular diseases were common COD in > = 70yo. Conclusion: Select septuagenarian LTX candidates may be safely transplanted with relatively few complications. Immunosenescence and conditions of the aged are likely contributing factors to the decreased rejection and graft failure observations. Septuagenarians should not be excluded from LTX consideration based solely on age. Transplantation in septuagenarians should only be done in very selected patients (screened for malignancies and atherosclerotic disease) and these recipients should be carefully followed after transplantation because of these risk factors.